The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1186/s12864-023-09429-8
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio-Sequins - dPCR-traceable DNA standards for quantitative genomics of Vibrio spp

Sabrina Flütsch,
Fabian Wiestner,
Lisa Butticaz
et al.

Abstract: Background Vibrio spp. are a diverse group of ecologically important marine bacteria responsible for several foodborne outbreaks of gastroenteritis around the world. Their detection and characterization are moving away from conventional culture-based methods towards next generation sequencing (NGS)-based approaches. However, genomic methods are relative in nature and suffer from technical biases arising from library preparation and sequencing. Here, we introduce a quantitative NGS-based method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…FNV38. More than 100 Vibrio species have been identified to date and they are ubiquitous gram-negative bacteria, found in a wide range of marine and aquatic temperate habitats (Flütsch et al 2023). Vibrio FNV38 was identified as part of a screening activity undertaken to mine organisms associated with Ulva thalli for ulvan and cellulose saccharifying enzymes (Rodrigues et al 2017) where it was shown to have activity on these substrates.…”
Section: Introductionmentioning
confidence: 99%
“…FNV38. More than 100 Vibrio species have been identified to date and they are ubiquitous gram-negative bacteria, found in a wide range of marine and aquatic temperate habitats (Flütsch et al 2023). Vibrio FNV38 was identified as part of a screening activity undertaken to mine organisms associated with Ulva thalli for ulvan and cellulose saccharifying enzymes (Rodrigues et al 2017) where it was shown to have activity on these substrates.…”
Section: Introductionmentioning
confidence: 99%